EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMK NEGERI 6 PEKANBARU - Nurvitasari, Lusi; Suarman, Suarman; Gimin, Gimin (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Seeing the declining student learning outcomes shows that students' learning motivation towards the material is also quite low. The media that is considered appropriate and appropriate to current conditions is the Articulet Storyline learning media. The aim of this research is to analyze the level of effectiveness of using the Articulate Storyline learning media in increasing students' learning motivation at SMK Negeri 6 Pekanbaru. The population in this study is all class XI accounting at SMK Negeri 6 Pekanbaru, with the sample taken being one class. with a total of 35 students. Research data was collected using observation sheets and questionnaires as instruments. The analysis techniques in this research are descriptive analysis, prerequisite test, N-Gain test and hypothesis test. The research results show that the Articulate Storyline learning media is effective in increasing students' learning motivation at SMK Negeri 6 Pekanbaru. Analysis of hypothesis testing using the Paired Sample t test shows a significance of 0.05 where 0.000 < 0.05. This means that there is a significant difference in the learning motivation of students who use the Articulet Storyline learning media compared to those who do not use the Articulet Storyline learning media at SMK Negeri 6 Pekanbaru. Researchers concluded that the Articulet Storyline learning media was effective in increasing students' learning motivation in accounting subjects at SMK Negeri 6 Pekanbaru.